Impact of CO2-water-coal on enhanced coalbed methane recovery by CO2 injection in Huainan coalfield - Helong ZHANG; Shiqi LIU; Yuchen TIAN; Wenkai WANG; Shuxun SANG; Sijian ZHENG; Bing LI; Yongchun CHEN (Meitan kexue jishu)
CO2-enhanced coalbed methane recovery (CO2-ECBM) is a key method for CO2 geological utilization and sequestration. It holds promise for addressing challenges such as soft, low-permeability coal seams with difficult gas extraction, poor development performance, rapid production decline, and low recovery rates, as exemplified by the Huainan coalfield. The geochemical interactions of CO2 injection into coal seams and inorganic minerals in coal can alter the pore-fracture structure and permeability of the coal, significantly influencing CO2 sequestration capacity and methane production enhancement. Therefore, considering the effects of effective stress, temperature, and geochemical interactions—including competitive adsorption, diffusion, seepage of CO2 and CH4, and CO2-water-coal geochemical interactions, as well as their impact on the dynamic evolution of coal seam porosity and permeability—a fully coupled Thermo-Hydro-Mechanical-Chemical mathematical model was developed for the seepage-stress-temperature-chemical interactions in CO2-injected coal reservoirs. Numerical simulation studies on CO2-ECBM were conducted for the Huainan coalfield to analyze the effect of geochemical interactions on CH4 production enhancement during CO2 injection, as well as the influence of injection pressure, initial permeability, and water saturation on CH4 production and CO2 sequestration. The results showed a high degree of consistency between the mathematical model and experimental outcomes, with the average error range for CH4 and CO2 mixture volumetric fractions and production rates falling within 1%−10%. Compared to scenarios ignoring CO2-water-coal geochemical interactions, the cumulative CH4 production decreased by 11%, while cumulative CO2 storage increased by 19.8%, indicating that neglecting geochemical interactions could lead to an overestimation of CH4 production and underestimation of CO2 storage capacity. Higher injection pressures and initial permeability of coal reservoirs resulted in more significant CH4 production enhancement and CO2 sequestration, whereas high water saturation adversely affected both processes. These findings suggest that CO2-ECBM should be tailored to reservoir properties, optimizing target layers and injection strategies to maximize CH4 production and CO2 storage. Geochemical interactions were found to alleviate the reservoir pressure increase caused by CO2 injection, reduce the free-state CO2 content in fractures. This, in turn, mitigated permeability decline due to stress-strain effects, promoting permeability recovery by 2.4%−3.3%. The permeability recovery further facilitated pressure transmission, CO2 adsorption, and CH4 desorption/diffusion, ultimately enhancing CH4 production and CO2 sequestration efficiency.